Assessing agroecosystem resilience in annual cropping systems with ecometabolomics - Andrea K. Clemensen; Henriette Uthe; Jianghao Sun; Sara E. Duke; Mark A. Liebig; Craig W. Whippo; David W. Archer (Agrosystems, Geosciences & Environment, 2025)
Abstract Plant ecometabolomics is a growing field of study that allows broader understanding of the metabolomic dynamics within and between plants and their ecosystem. Plants constantly respond to environmental cues, producing plant secondary metabolites (PSMs) to communicate with and adapt to their ever‐changing ecosystems. PSMs allow plants to withstand biotic and abiotic stressors and are mediators of interactions between their aboveground and belowground ecosystem. However, the way PSMs are affected by and respond to agricultural management is poorly understood. As part of the long‐term agroecosystem research network, we assessed ecometabolomic profiles of corn (Zea mays L.) leaves and roots between contrasting prevailing (prevailing practice, PP) and alternative (alternative practice, AP) cropping practices, which utilized cover crops and cover crop interseeding. The ecometabolomic profiles of corn leaves and roots were 90% and 71%, respectively, richer in PSMs in the AP than PP treatments. Our untargeted metabolomic analyses resulted in 124 annotated features, with 68 features significantly different between AP and PP treatments. We detected 43 features annotated as PSMs, 39 of which were greater (p ≤ 0.10) in the AP than PP treatments. This research shows that our agricultural management practices influence the way plants respond within their agroecosystem. Increased production of PSMs allows plants to better adapt to various abiotic and biotic stresses, enhancing the resilience of plants within their ecosystem.